OneHealth Approaches Contribute Towards Antimicrobial Resistance: Malaysian Perspective - Mariappan, Vanitha; Vellasamy, Kumutha Malar; Mohamad, Nor Alia; Subramaniam, Sreeramanan; Vadivelu, Jamuna (Frontiers in Microbiology, 2021)
On a global scale, antimicrobial resistance (AMR) is recognized as a One Health challenge due to the continual and increased development and distribution of resistant microbes and genes among humans, animals, and the environment. These sectors contribute to the increase in AMR, as antibiotics are widely used in healthcare to treat or prevent bacterial infection; as growth enhancers, therapeutics and metaphylactics in animal husbandry; and transmitted in the environment through irrigation using wastewater or inappropriate disposal and treatment of human and agricultural waste. However, there is a major drawback in terms of the lack of research assessing the coexistence of AMR in these sectors. Extensive research highlighted food–animal manufacture structures that are likely to harbor reservoirs or promote transmission of AMR, in addition to increasing human colonization with AMR commensal bacteria. Numerous antibiotic stewardship policies have been designed and implemented in medical practices and animal husbandry in high- and middle-income countries. However, research concentrating on high-income settings, attitudes, emotions, and beliefs on the utilization of antimicrobials remain underexplored in lower- and middle-income countries such as Malaysia. Microbiological, epidemiological, and social science exploration are required at community and farming across the One Health range to fill huge gaps in information and knowledge of AMR. Manipulating human activities and character associated with antibiotics is a multifaceted progression that includes elements like knowledge, social behavior, attitudes, approaches, social standards, socioeconomic settings, peer pressure, experiences, and biophysical environment. Therefore, understanding these aspects in the utilization of antimicrobial drugs among the different sectors is essential to develop and implement policies to curb AMR development and transmission that overarch all sectors within the One Health consortium in Malaysia.